Discussion on Relationship Between Temperature-Pressure-Adsorption and Coal and Gas Outburst - LI Dong, ZHANG Xuemei, HAO Jingyuan, MA Qinghua (Meikuang Anquan, 2020)
The relationship between temperature-pressure-adsorption of raw coal and deformed coal of Daning Coal Mine is calculated by using a series of isotherm adsorption experimental data. The results show that the adsorption process is an exothermic process. The isosteric enthalpy of adsorption, the unit isosteric enthalpy of adsorption, and the unit isosteric enthalpy of desorption are defined. When the adsorption capacity is 45 cm3/g, the unit isosteric heat of desorption of deformed coal is 0.158 kJ/(mol·cm3·g) less than that of raw coal. Compared with the normal coal, the deformed coal is preferred to desorption; compared with the exothermic process, the buried depth strengthens the desorption; compared with the raw coal, the deformed coal is easier to extract the necessary energy for desorption from the environment. Compared with raw coal, the low permeability and low firmness coefficient of deformed coal are more likely to lead to coal and gas outburst.